2015
DOI: 10.1111/ene.12887
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of return to work after stroke in patients with mild−moderate disability in India

Abstract: Background Successful return to work after stroke may improve economic circumstances, quality of life and overall life satisfaction, but not all stroke survivors are able to return to work. Aim Our aim was to determine what proportion of previously employed patients return to work after an acute stroke resulting in mild to moderate disability and to examine factors associated with a successful return to work. Methods Patients 18–60 years of age who were previously employed and who had a first‐ever stroke 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 29 publications
0
41
0
2
Order By: Relevance
“…24,49,65,66,7586 Some single remaining studies on activities such as eating, exercise or leisure 30,31,8790 did not fit this format. In all the types of valued activities social support was identified as a facilitator to reengagement.…”
Section: Resultsmentioning
confidence: 99%
“…24,49,65,66,7586 Some single remaining studies on activities such as eating, exercise or leisure 30,31,8790 did not fit this format. In all the types of valued activities social support was identified as a facilitator to reengagement.…”
Section: Resultsmentioning
confidence: 99%
“…Bonner et al. (2016) reported that 52.5% returned to work after 3 months to 2 years post stroke in a relatively young group (<60 years old), with mild to moderate stroke (mRS ≤ 3) in India. In comparison, 17% in the urban area and 11% in the rural area return to work in China at 1 year post discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke may impose disabilities with severe consequences for the individual, not only in the physical and psychological sense but also with regard to the patient's social situation, work, and family relations. Return to work (RTW) has been shown to improve their overall life satisfaction as well as economic circumstances (Bonner et al., 2016; Treger, Shames, Giaquinto, & Ring, 2007; Vestling, Tufvesson, & Iwarsson, 2003). Factors influencing the RTW after stroke have been related to the financial and intrinsic aspects of the work and focused less on its social aspects (Vestling et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Mit ihrer Hilfe kann der Schweregrad des neurologischen Defizits nach einem Schlaganfall erfasst werden, wobei ein Wert von "0" kein neurologisches Defizit und ein Wert von "5" eine schwere Behinderung (Patient ist bettlägerig, inkontinent und beaufsichtigungspflichtig) beschreibt [23]. Ein niedriger Wert in der Rankin-Skala ist dabei mit einer erfolgreichen Reintegration auf dem Arbeitsmarkt assoziiert [24]. Demnach könnte ein niedriger GdB sowie damit vergleichbare analoge internationale Faktoren wie ein niedriger Rankin-Skala Wert [24] und keine motorischen-und kognitiven Einschränkungen [19] mögliche Prognosefaktoren für eine berufliche Reintegration darstellen.…”
Section: Diskussionunclassified